Chlorophytum tillariense (Asparagaceae), a new species from Western Ghats of India - Chandore, Arun Nivrutti; Yadav, Shrirang Ramchandra (Phytotaxa, 2019)
Chlorophytum tillariense, a new species of Chlorophytum from high altitudinal lateritic plateaus of Tillari area of Maharashtra, India, is described and illustrated. The new species is closely related to C. gothanense, which was recently described from the same region of Gothane village in Western Ghats. Coloured photographs and illustrations are provided to facilitate the identification.